Integrasi Need Assessment dan Key Performance Indicators dalam Penjaminan Mutu Pendidikan Tinggi Islam: Systematic Literature Review - Adib Rofiuddin Basori; Mulyawan Safwandy Nugraha; Ai Asiah; Ahmad Bahrul Hayat (Sekolah Tinggi Ilmu Tarbiyah Buntet Pesantren Cirebon, 2026)
This article aims to synthesize recent findings on the integration of needs assessment and key performance indicators (KPIs) in the quality assurance of Islamic higher education and to formulate a more integrative theoretical model. The review was compiled following the PRISMA 2020 standards. A literature search was conducted on April 4, 2026, through various journal portals and online scientific databases with a publication period of 2021–2025. Keywords used included needs assessment, KPI, quality assurance, Islamic higher education, SPMI, and accreditation. After going through the stages of identification, deduplication, title and abstract screening, and full-text review, a total of 16 studies were included in the final synthesis. The review results indicate that the literature remains fragmented into three main streams: needs assessment studies that focus on curriculum development; KPI studies that predominantly focus on dashboards, reporting, and performance measurement; and quality assurance studies of Islamic higher education that emphasize governance, accreditation, and quality culture. The main findings indicate the absence of a model that explicitly links stakeholder needs, KPI formulation, the SPMI/PPEPP cycle, and the internalization of Islamic values ​​within a unified quality system. Based on this conceptual synthesis, this article proposes the V-NAKPI-QA model as a sustainable quality assurance framework that integrates Islamic values, participatory needs assessment, tiered KPIs, and data-driven feedback